English hepatitis C registry data show high response rates to directly acting anti‐virals, even if treatment is not completed. Issue 1 (22nd May 2020) - Drysdale, Kathryn; Ntuli, Yevedzo; Bestwick, Jonathan; Gelson, William; Agarwal, Kosh; Forton, Daniel; Mutimer, David; Elsharkawy, Ahmed M.; Townley, Ceri; Mahomed, Faizel; Foster, Graham R.
Summary: Background: In England, choice of hepatitis C therapy is determined by national contracts that change with time, facilitating comparisons between different regimens. England has a diverse population with hepatitis C including large proportions of uncommon viral genotypes. Aim: To evaluate efficacy of directly acting anti‐viral treatments for hepatitis C in England using real‐world data from the national treatment registry. Methods: Sustained virological response (SVR) rates 12 weeks after treatment completion for patients treated between 2014 and August 2018 who attended for SVR tests were analysed in univariate subgroups using Chi‐squared tests. Multivariate models were constructed with clinically relevant variables to determine predictors of SVR and evaluate the impact of treatment regimens. Results: SVR data were available on 14, 603 treated patients. The overall SVR rate was 95.59% [95% CI 95.25%‐95.91%]. Multivariable regression modelling in patients with genotype 1 infection showed that the odds of SVR with elbasvir/grazoprevir were higher than for those treated with sofosbuvir/ledipasvir (OR 1.891, 95% CI 1.072‐3.336, P  = 0.028). For genotype 3, we found no significant difference between any of the treatment regimens. Patients who completed at least one third of the planned treatment duration achieved SVR rates in excess of 80%. Conclusions: All of the currently licensed hepatitis C direct‐acting anti‐viral regimens had similar efficacy (>95%) in an unselected population. Noncompletion of planned treatment duration still resulted in over 80% SVR rates provided that more than one third of treatment was completed.